Find the least possible value of a + b where a , b are positive integers such that 1 1 divides a + 1 3 b and 1 3 divides a + 1 1 b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
(a+13b) = 0 (mod 11) and (a+11b) = 0(mod 13)
now 13 times a multiple of 11 and
11 times a multiple of 13 is divisible by 11*13 = 143.
therefore 13*(a+13b) = 0 (mod143)
and 11*(a+11b) = 0 (mod 143)
hence
13 a + 169b = 0 (mod 143)
and 11a + 121b = 0 (mod 143)
adding both gives: 24a + 290b = 0 (mod 143)
2(12a + 145b) = 0 (mod 143)
that implies
12a + 145b = 0(mod 143)
(12a + 2b) + 143b = 0 (mod 143)
that implies
12a + 2b = 0 (mod 143)
2(6a+b) = 0 (mod 143)
hence a = 143/6 = 23
and b = 143 - 23*6 = 5.
a+b = 28.
a + 1 3 b ≡ a + 2 b ≡ 0 ( m o d 1 1 ) .
Multiplying by 6 , 6 a + 1 2 b ≡ 0 ( m o d 1 1 ) which further implies 6 a + b ≡ 0 ( m o d 1 1 ) .
Again, a + 1 1 b ≡ a − 2 b ≡ 0 ( m o d 1 3 )
Multiplying by 6 , 6 a − 1 2 b ≡ 0 ( m o d 1 3 ) which implies 6 a + b ≡ 0 ( m o d 1 3 ) .
Since g c d ( 1 1 , 1 3 ) = 1 ,therefore 1 4 3 divides 6 a + b .
So we can write, 6 a + b = 1 4 3 k , or 6 a + 6 b = 1 4 3 k + 5 b = 1 1 4 k + 6 b − ( k + b )
Hence, 6 divides k + b and so, k + b ≥ 6
Now, 6 ( a + b ) = 1 4 3 k + 5 b = 1 3 8 + 5 ( k + b ) ≥ 1 3 8 + 3 0 = 1 6 8
Hence, a + b ≥ 2 8
Taking, a = 2 3 and b = 5 , one can see the conditions of the pronlem are satisfied.
So,the minimum value of a + b is 2 8
1 1 ∣ a + 1 3 b ⟹ 1 1 ∣ ( a + 1 3 b ) + 1 1 b ⟹ 1 1 ∣ a + 2 4 b
1 3 ∣ a + 1 1 b ⟹ 1 3 ∣ ( a + 1 1 b ) + 1 3 b ⟹ 1 3 ∣ a + 2 4 b
Since a + 2 4 b is a multiple of 1 1 and 1 3 and these numbers are coprime, it follows that a + 2 4 b is a multiple of 1 1 × 1 3 = 1 4 3
Since we want the least possible value of a + b , we need to set a + 2 4 b = 1 4 3 and maximize b
Under these conditions, a = 2 3 and b = 5 , so a + b = 2 8
a + 1 3 b ≡ 0 ( m o d 1 1 ) ⇒ a + 2 b ≡ 0 ( m o d 1 1 )
a + 1 1 b ≡ 0 ( m o d 1 3 ) ⇒ a − 2 b ≡ 0 ( m o d 1 3 )
a − 2 b = 1 3 x
Let x = 1 (For the smallest value of a+b)
1 7 − 4 = 1 3 ⇒ 1 7 + 4 = 2 1 ≡ − 1 ( m o d 1 1 )
1 9 − 6 = 1 3 ⇒ 1 9 + 6 = 2 5 ≡ 3 ( m o d 1 1 )
2 1 − 8 = 1 3 ⇒ 2 1 + 8 = 2 9 ≡ 7 ( m o d 1 1 )
2 3 − 1 0 = 1 3 ⇒ 2 3 + 1 0 = 3 3 ≡ 0 ( m o d 1 1 )
s o , b = 1 0 / 2 = 5
H e n c e ( a , b ) = ( 2 3 , 5 ) ⇒ a + b = 2 8
Problem Loading...
Note Loading...
Set Loading...
Given that 11 divides a + 1 3 b and 13 divides a + 1 1 b , we know that
a + 1 3 b ≡ 0 ( m o d 1 1 )
and
a + 1 1 b ≡ 0 ( m o d 1 3 ) .
These are equivalent to
a + 2 b ≡ 0 ( m o d 1 1 )
and
a − 2 b ≡ 0 ( m o d 1 3 ) .
Now, let a + 2 b = 1 1 j and a − 2 b = 1 3 k , where j , k are non-negative integers. Because b is positive, 1 1 j must be bigger than 1 3 k as there is a difference of 4 b between the two equations. This means that j > k .
If we add the two equations, we get
2 a = 1 1 j + 1 3 k .
Ideally we want a as small as possible, which means we are looking for the smallest values of j and k that work. As j and k are integers, 1 1 j and 1 3 k must add to give an even number ( 2 a ).
The smallest values of j and k that fit these criteria are 2 and 0 (respectively). This leads to a being 11. Looking back to our equation a − 2 b = 1 3 k , the only non-negative value of 1 3 k that is smaller than 11 is 0. This leads to b being 5.5, however we know that b is an integer, so this cannot be the case.
The next smallest values of j and k are 3 and 1. This leads to a being 23.
Using these values we can try to find b by subtracting the two equations instead, giving
4 b = 1 1 j − 1 3 k .
If we substitute our values in, we get
4 b = 1 1 ⋅ 3 − 1 3 ⋅ 1 = 2 0
b = 5
b is an integer! It works!
Therefore
a + b = 2 3 + 5 = 2 8
This is my first time using latex (and writing a solution!), so sorry if my write-up is a bit wonky.